Generational increase in obesity among young women: A prospective analysis of mother-daughter dyads - Alati, Rosa; Betts, K.; Williams, G.; Najman, J.; Zalbahar, N.; Mamun, A. (Nature Publishing Group, 2016)
© 2016 Macmillan Publishers Limited. All rights reserved. Background/Objectives:Increases in obesity in young adults over recent decades are shown by national survey data but have yet to be replicated using prospective data. We aim to quantify the increase in obesity and overweight over two generations of young adult women using prospective measures of body mass index (BMI).Subjects/Methods:Data are from the Mater University Study of Pregnancy (MUSP), a prospective pre-birth cohort study started in 1981 in Brisbane, Australia. Analyses were restricted to 992 mother-daughter dyads who were at similar ages at the time they were assessed and for whom measures of BMI were available. We also conducted an additional analysis to test whether there was a similar increase amongst father-son dyads. We used multinomial logistic regression for clustered data to compare the same prospective measures of BMI categories between mother and daughters.Results:Controlling for a number of sociodemographic and lifestyle factors in the female sample, daughters had 5.04 (3.03, 8.85) times the odds of being obese and 2.54 (1.86, 3.54) times the odds of being overweight compared with their mothers. A large increase in obesity was also observed in the male sample.Conclusions:Using a longitudinal design to partly account for familial confounding of obesity risk factors, this study confirms a large and concerning increases in obesity rates over two generations of young adults and suggests increases in obesity over the past 20 years may be greater than previously anticipated.